1993
DOI: 10.1039/c39930000183
|View full text |Cite
|
Sign up to set email alerts
|

The isolation and X-ray structure determination of an active intermediate in the accelerated sulfur vulcanization of alkenes

Abstract: In the sulfur vulcanization reaction of Zr3-dimethylbut-2-ene (C&12), in the presence of S8, ZnO and organic accelerators, intermediate products are formed, which consist of an alkene bound by sulfur t o an accelerator fragment: C6H1 1-S,-S(S)CNMe2, where n 2 0; the isolation, characterisation and vulcanization activity of 2,3-dimethylbut-2-en-I -yl dimethyltrithiopercarbamate 1-S-S(S)CNMe2] is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…It is known that ZDC contains very small amounts of thiuram, which can initiate the sulfur exchange reactions during vulcanization [19,20]. Xanthates are much more effective accelerators compared to dithiocarbomates because of the presence of the oxygen atom.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that ZDC contains very small amounts of thiuram, which can initiate the sulfur exchange reactions during vulcanization [19,20]. Xanthates are much more effective accelerators compared to dithiocarbomates because of the presence of the oxygen atom.…”
Section: Resultsmentioning
confidence: 99%
“…Disulfide‐containing compounds are of considerable biological1 and technological relevance,2 and the mechanisms by which the sulfur−sulfur bond in these compounds can be reversibly broken and formed has attracted a great deal of interest 3. We have recently reported that nucleophilic degradation of cyclooctasulfur by the diphosphanylmethanide complex of manganese( I ) [Mn(CO) 4 {(PPh 2 ) 2 CH}] allows the formation of the hexasulfur‐bridged bis(diphosphanylmethanide) dimetallic derivative [(CO) 4 Mn{(PPh 2 ) 2 C−S 6 −C(PPh 2 ) 2 }Mn(CO) 4 ] 4.…”
Section: Methodsmentioning
confidence: 99%
“…The most important and significant step in the two-stage vulcanization is the generation of rubber-bound moieties 1,17 from the accelerator complex with sulfur, etc. These rubberbound moieties, which are the precursor 18 to the ultimate crosslinks, are responsible for subsequent vulcanization. Thus, owing to the prior formation of these rubber-bound moieties, a reduction in scorch safety occurs in two-stage vulcanization.…”
Section: Two-stage Vulcanizationmentioning
confidence: 99%